2016
DOI: 10.1292/jvms.16-0022
|View full text |Cite
|
Sign up to set email alerts
|

Development of a preliminary diagnostic measure for bovine leukosis in dairy cows using peripheral white blood cell and lymphocyte counts

Abstract: Analysis of the association between antibodies against bovine leukemia virus (BLV), BLV proviral load, and white blood cell (WBC) and lymphocyte counts was performed with 774 dairy cows. The average age, WBC counts and lymphoid cell counts tended to be higher in BLV antibody-positive cows than in antibody-negative cows. There was a similar trend in levels of proviral DNA. We analyzed age, WBC counts and lymphocyte counts by principal component analyses to create a distribution chart of the principle component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…WBC count reference intervals (i.e., mean ± 2 SD) for BLV-negative and BLV-positive groups have been ranged from 5,906 to 16,609 WBCs/µL and from 4,710 to 29,322 WBCs/µL, respectively ( Table 2). Our results are consistent with the data of other authors, wherein the correlation of total WBC counts and BLV proviral loads in BLV-infected animals has been investigated [45,46]. It is despite the fact, that apart from BLV infection, the increase of the number of WBCs can be the consequence of inflammation, stress, injury, leukemia, and other infections [47].…”
Section: Discussionsupporting
confidence: 93%
“…WBC count reference intervals (i.e., mean ± 2 SD) for BLV-negative and BLV-positive groups have been ranged from 5,906 to 16,609 WBCs/µL and from 4,710 to 29,322 WBCs/µL, respectively ( Table 2). Our results are consistent with the data of other authors, wherein the correlation of total WBC counts and BLV proviral loads in BLV-infected animals has been investigated [45,46]. It is despite the fact, that apart from BLV infection, the increase of the number of WBCs can be the consequence of inflammation, stress, injury, leukemia, and other infections [47].…”
Section: Discussionsupporting
confidence: 93%
“…In these guidelines, the test and segregate or test and manage strategy is recommended, and diagnostic methodologies such as ELISA, qualitative PCR, and quantitative real-time PCR were introduced; however, methodologies to follow were not strictly specified. Real-time PCR and ELISA are widely used in Japan to identify BLV-infected dairy cattle (Nishiike et al, 2016). The test and segregate or test and manage strategy has been practiced in Argentina as well (Gutiérrez et al, 2011(Gutiérrez et al, , 2012Alvarez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some groups suggested that cattle with high PVL are efficient transmitters (Gutiérrez et al, 2014;Ohno et al, 2015). Although advantages to using real-time PCR exist, this technique has not been used in Japan as a uniformed routine tool in the national control program because of the high cost and complex equipment required (Nishiike et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide the prevalence of BLV is varied, in studies performed in Asia the prevalence of BLV is higher than this research, for example, in the prefecture of Osaka, Japan, a total of 774 dairy cows over 48 months of age were sampled and the prevalence of BLV was of 60.33% (43), other study in nine provinces of Thailand (44), found a seroprevalence of BLV between 11.0 to 100%. But in a study in four provinces of Cambodia sero-prevalence of the BLV was between 0 to 16.8% (45) and , in four township of Myanmar a prevalence of 9.1% was found (46), being both lower than this research.…”
Section: Discussionmentioning
confidence: 53%
“…Other study in five prefectures of Japan showed a sero-prevalence at level of herds between 47 to 61% (2). In Argentina the prevalence in herd was of 84% (43).On the contrary, in Italy the prevalence in herds was of 0.08% (49). In Iran, prevalence in farms was of 43.9% (59).…”
Section: Discussionmentioning
confidence: 99%